Highly dispersed nano-enzyme triggered intracellular catalytic reaction toward cancer specific therapy. (November 2020) - Mei, Xuan; Hu, Tingting; Wang, Hui; Liang, Ruizheng; Bu, Wenbo; Wei, Min
Abstract: Currently, reactive oxygen species (ROS)-induced apoptosis systems have drawn increasing attention in cancer therapy, owing to their specific tumor inhibition ability and great biocompatibility. Herein, we developed a highly dispersed nano-enzyme based on the assembly of natural glucose oxidase (GOD) onto CoFe-layered double hydroxides (CoFe-LDHs) monolayer nanosheets. By virtue of the high dispersion of Fe 3+ within the host layer, the CoFe-LDHs nanosheets exhibit a collaborative enhanced Fenton catalytic activity with a rate constant of 3.26 × 10 −4  s −1, which is 1–3 orders of magnitude higher than other iron-containing Fenton reaction agents. Subsequently, with a massive H2 O2 triggered by GOD, GOD/CoFe-LDHs nanohybrid converts a cascade of glucose into hydroxyl radicals under tumor acid conditions, which is validated by a high maximum velocity ( V max  = 2.23 × 10 −6  M) and low Michaelis–Menten constant ( K M  = 5.40 mM). Through the intracellular catalytic Fenton reaction within the tumor environment, both in vitro and in vivo results demonstrate the excellent antitumor effect of GOD/CoFe-LDHs. Therefore, a self-supplied, ultra-efficient and sequential catalytic tumor-specific therapy has been achieved based on GOD/CoFe-LDHs nano-enzyme, which holds great promise in clinical cancer therapy with minimum side effects. Graphical abstract: Highly dispersed GOD/CoFe-LDHs nano-enzyme is fabricated by immobilizing natural glucose oxidase (GOD) onto CoFe-LDHs monolayer nanosheets, which provides a paradigm for cancer specific therapy through self-supplied and ultra-efficient intracellular Fenton reaction. Image 1